Organising stakeholder workshops in research and innovation – between theory and practice - Bjørn Bedsted; Morten V. Nielsen; Nina Bryndum (Journal of Deliberative Democracy)
This article addresses the theory and practice of creating responsiveness among actors through deliberative dialogue processes with stakeholders from diverse institutional settings. The EU’s decision to mainstream stakeholder deliberation in research and innovation, as part of its focus on responsible research and innovation (RRI), creates a new potential for experimentation and integration of deliberative processes. The article presents a list of essential considerations for three steps in the workshop process: planning and design, workshop interaction and the gathering of conclusions. Finally, the article illustrates the challenges of applying theory to five European stakeholder workshops co-organised by the authors. The illustration highlights the difficult interaction between theory and practice. The article concludes that while theoretical perspectives can provide general guidance, practical experience is essential when dealing with the trade-offs that are an intrinsic part of organising stakeholder workshops.